Pengaruh Product Knowledge, Brand Image Dan Celebrity Endorser Terhadap Keputusan Pembelian Mikrofon Seruniaudio di PT. Seruni Karya Indonesia - Dony Buntoro; Fathorrahman; Theresia Pradiani (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
This study aims to analyze the effect of Product Knowledge, Brand Image, and Celebrity endorsers on the Purchase Decision of SeruniAudio Microphone at PT. Indonesian Artwork. This study uses a quantitative approach. The number of respondents in this study was 100 respondents who had bought SeruniAudio microphones, using the Simple Random Sampling technique. The results of this study indicate, among others: 1) Product Knowledge has a positive and significant effect on purchasing decisions; 2) Brand Image has a positive and significant effect on purchasing decisions; 3) Celebrity Endorser has a positive and significant effect on the decision to purchase a SeruniAudio microphone